2015
DOI: 10.1159/000381019
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an Effective Radioiodide Thyroid Ablation Protocol in Mice

Abstract: Due to the high variance in available protocols on iodide-131 (131I) ablation in rodents, we set out to establish an effective method to generate a thyroid-ablated mouse model that allows the application of the sodium iodide symporter (NIS) as a reporter gene without interference with thyroidal NIS. We tested a range of 131I doses with and without prestimulation of thyroidal radioiodide uptake by a low-iodine diet and thyroid-stimulating hormone (TSH) application. Efficacy of induction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
5
0
1
Order By: Relevance
“…In our current study, in addition to the decrease in serum TH, hepatic DIO1, a key enzyme that activates TH and converts thyroxine to triiodothyronine, is also downregulated in GH and PH groups, which matches up with previous study [34,35]. The mechanism for the regulation of SREBP1c by TH has remained controversial.…”
Section: Discussionsupporting
confidence: 88%
“…In our current study, in addition to the decrease in serum TH, hepatic DIO1, a key enzyme that activates TH and converts thyroxine to triiodothyronine, is also downregulated in GH and PH groups, which matches up with previous study [34,35]. The mechanism for the regulation of SREBP1c by TH has remained controversial.…”
Section: Discussionsupporting
confidence: 88%
“…LPEI has been shown to exhibit certain cytotoxic effects both in vitro and in vivo [ 37 41 ], though LPEI-based polyplexes have already been tested in a clinical trial for bladder cancer therapy and no adverse effects were reported [ 42 ]. Similarly, we have so far only encountered side effects from 131 I in one previous study with the objective to radioablate mouse thyroids under intentional stimulation of thyroidal radioiodide uptake [ 43 ]. Symptoms developed with a delay of seven days after radioiodide application, while in the current study, animal health deteriorated from the beginning of treatment [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, 131 I doses ranging from 1.04 to 37 MBq (28–1000 μCi) were used in previous thyroid ablation reports 21 , 24 – 26 . The 131 I ablation dose can produce systemic and local adverse effects, including weight loss, salivary gland dysfunction, tracheal damage, and breathing difficulty 32 , 33 . Higher doses tends to show higher ablation success rates, but more frequent adverse effects 34 .…”
Section: Discussionmentioning
confidence: 99%